COVER AND PREFACE JURNAL KONVERSI ENERGI DAN MANUFAKTUR VOL. 9 NO. 2 (2024) - Jurnal Konversi Energi dan Manufaktur Editor's (Jurnal Konversi Energi dan Manufaktur, 2024)
SUMMARY. Saputro and Golwa, in their paper, developed a blade generator system for generating electrical energy from wasted wind in AC condensers. In their paper, Sopiyan et al. conducted hard-facing using the SMAW process and added titanium to the weld layer to increase hardness and corrosion resistance. Anggraini et al., in their paper, conducted research to obtain the productive percentage and operator workload level on the SVC93E20PBE compressor assembly line for the R600A refrigerator unit. Sugiyanto et al., in their paper, conducted research to determine the effect of temperature and pressure on the thickness and shrinkage of 30 ml bottle molds. Maulidah et al., in their paper, compared the resistance of the BCM-3 ship with a conventional hull and the BCM-4 ship with a bulbous bow hull. Chandra et al., in their paper, manufactured Mg2Si-based thermoelectric materials with bismuth doping using a solid-state reaction method using a powder technique in a sealed tube. Syaripuddin et al., in their paper, carried out hard facing on carbon steel surfaces using HV-800 electrodes with various thicknesses to see the hardness and corrosion of the weld layer. In addition, distortions were also observed in the post-welding specimens. Muliastri et al., in their paper, carried out welding on 6 mm AISI 1045 steel with varying currents of 75, 85, and 95 A to see the effect on the tensile strength and Vickers hardness tests.